Robust H∞ Control Implementation in IFOC for High-Performance Electric Vehicle Induction Motors - Boudallaa Abdelhak; Chennani Mohammed; Belkhadir Ahmed; Rhofir Karim; Belkhayat Driss (ITM Web of Conferences, 2024)
This paper presents an indirect field-oriented control method with rotor flux orientation applied to induction motors, enhanced by robust controllers. This approach aims to optimize the motor's dynamic performance, allowing for more precise control of torque and speed. Due to the nonlinear, multivariable, and highly coupled dynamics, induction motors require particularly complex control algorithms. Consequently, this method relies on accurate knowledge of the rotor position, which is directly related to the rotor time constant and, under real conditions, depends on temperature variations as well as the magnetic state of the machine. This technique was simulated in MATLAB/Simulink environment and subsequently implemented in real time.